2018
DOI: 10.1186/s12883-017-1008-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma long non-coding RNA BACE1 as a novel biomarker for diagnosis of Alzheimer disease

Abstract: BackgroundsLong non-coding RNA (LncRNA) have been reported to be involved in the pathogenesis of neurodegenerative diseases, but whether it can serve as a biomarker for Alzheimer disease (AD) is not yet known.MethodsThe present study selected four specific LncRNA (17A, 51A, BACE1 and BC200) as possible AD biomarker. RT-qPCR was performed to validate the LncRNA. Receiver operating characteristic curve (ROC) and area under the ROC curve (AUC) were applied to study the potential of LncRNA as a biomarker in a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 40 publications
0
98
0
3
Order By: Relevance
“…This leads to the production of more Aβ 42 and an increase in the formation of SPs in the brain in AD patients, aggravating the development of the disease. Feng et al found that the level of the BACE1 is increased in the plasma of AD patients and that it has a high specificity (88%) for AD, indicating BACE1 may be a potential candidate biomarker to predict AD (Feng et al, 2018 ). Recently, Yang et al, investigated the hippocampal expression patterns of dysregulated lncRNAs in a rat model of AD through microarray (Yang et al, 2017 ).…”
Section: The Role Of Lncrnas In Neurodegenerative Diseasesmentioning
confidence: 99%
“…This leads to the production of more Aβ 42 and an increase in the formation of SPs in the brain in AD patients, aggravating the development of the disease. Feng et al found that the level of the BACE1 is increased in the plasma of AD patients and that it has a high specificity (88%) for AD, indicating BACE1 may be a potential candidate biomarker to predict AD (Feng et al, 2018 ). Recently, Yang et al, investigated the hippocampal expression patterns of dysregulated lncRNAs in a rat model of AD through microarray (Yang et al, 2017 ).…”
Section: The Role Of Lncrnas In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Upregulation of BC200 promotes BACE-1 activity and plasticity failure in AD postmortem brain tissues. Moreover, BC200 upregulation potentiates Aβ42 expression via a direct promotion of BACE-1 expression and subsequent impairment of cell viability [84][85][86]. The level of neuroblastoma differentiation marker 29 (NDM29) is increased by inflammation.…”
Section: Ncrnas In the Regulation Of Aβ Generation And Accumulationmentioning
confidence: 99%
“…In AD patient brains, NDM29 upregulation induces APP synthesis and promotes its cleavage by BACE1 and γ-secretase. Upregulation of BC200 or NDM29 increase Aβ secretion and the Aβ42/40 ratio [85,86]. BACE1-AS is a conserved RNA transcribed from the opposite strand of the BACE1 locus on chromosome 11 (11q23).…”
Section: Ncrnas In the Regulation Of Aβ Generation And Accumulationmentioning
confidence: 99%
“…Altered lncRNA transcription may be involved in increasing the risk of AD. There is evidence for several specific lncRNAs being dysregulated in AD, including APP, and BACE1 [128]. Such altered expression is detectable not only in AD brain, but also in the plasma and CSF of these patients [128][129][130][131].…”
Section: Long Non-coding Rnas (Lnc-rnas)mentioning
confidence: 99%
“…There is evidence for several specific lncRNAs being dysregulated in AD, including APP, and BACE1 [128]. Such altered expression is detectable not only in AD brain, but also in the plasma and CSF of these patients [128][129][130][131]. In particular, BACE1-AS lncRNA is an antisense RNA transcribed by RNA polymerase II from the complementary strand of BACE1 in the locus 11q 23.3 [132]; it is directly implicated in the increased abundance of Aβ 1-42 in AD.…”
Section: Long Non-coding Rnas (Lnc-rnas)mentioning
confidence: 99%